A Study of Top Management Support Onto BIM Adoption in China Consulting Companies - Qin, Yi Ying (2021)
Top management support is a crucial driver for consulting companies in China's architecture, engineering and construction (AEC) industry. They must identify changes in the competitive environment, which are becoming increasingly technical. In addition, top management must respond most efficiently and effectively possible. Currently, China consulting companies which using BIM are subject to changes of organizational contexts and top management support that influences the BIM application. This study focuses on this phenomenon through analyzing the variables of top management support and organizational readiness affecting BIM usage. This paper uses qualitative research to analyze data output based on interviews with ten China consulting companies. The aim of the analysis is to find evidence from the above mentioned relationship using the Technology-Organization-Environment (TOE) framework. Besides that, organizational readiness to increase BIM adoption in consulting companies with top management support is also studied. The findings highlight that top management support and the need to provide organizational readiness for companies to improve their technical capabilities are the essential prerequisites for BIM adoption in the companies. The contribution of this paper is to provide empirical evidence to show that the behaviour of top management support influences the effective adoption of BIM organizational factors in China consulting companies.